Is the Cyclical Component of the Debt Brake Still Up to Its Task? - Max Krahé; Florian Schuster; Philippa Sigl-Glöckner (Wirtschaftsdienst)
Abstract Debates around the German debt brake currently focus on the whether and how of constitutional reform. Yet, a key component of the debt brake — cyclical adjustment — is only specified in ordinary law. And upon closer inspection, it is precisely that part of the debt brake that is most in need of reform: The cyclical component in its current form does not incorporate recent research findings, creates excessive space for discretionary decision making without accountability, and has an ambivalent impact on the sustainability of public finances in the long term. A reform of the cyclical component of the debt brake, which does not require changing the constitution, could therefore be a pragmatic step towards a more sustainable fiscal policy regime in Germany.